Toccare il blu. Tracce di una aptologia a partire da Merleau-Ponty - Negri, Federica (Scenari, 2024)
The essay seeks to trace, from the Phenomenology of Perception to The Visible and the Invisible, an itinerary that can reveal the traces of a different way of doing philosophy, certainly belonging to a tradition that we could define, with Jacques Derrida, “a certain philosophical history of touch”. Letting ourselves be stimulated by the reading that Derrida offers in Le Toucher, Jean-Luc Nancy, a tribute text dedicated to his friend, we will try to reconstruct this philosophical history of touch, to compare Merleau-Ponty’s thought with that of Husserl and Nancy on this theme, but also to find perhaps unsuspected legacies from later philosophers.